HUBUNGAN FAKTOR RISIKO YANG DAPAT DI MODIFIKASI DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL DI PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI TAHUN 2023 - Ikhsan, Mulyadi; Fitri, Adelina; Sitanggang, Hendra Dhermawan; Wisudariani, Evy (Jurnal Kesmas Jambi, 2023)
Background : Hypertension in pregnant women is one of the causes of morbidity and mortality for both the mother and the fetus throughout the world. Globally it is known that (10%) pregnant women worldwide experience hypertension during their pregnancy. Simpang IV Sipin Health Center is one of the health centers with the highest number of cases of hypertension in pregnant women in Jambi City. The purpose of this study was to find out the relationship between modifiable risk factors and the incidence of hypertension in pregnant women at the Simpang IV Sipin Health Center, Jambi City in 2023. Methods : The design used in this study was case control with a total sample of 69 people consisting of 23 people for the case sample and 46 people for the control sample which was carried out in the Simpang IV Sipin Health Center work area, Jambi City. The variables examined in this study were physical activity, stress levels, obesity, exposure to cigarette smoke, salt consumption and fat consumption. Data analysis used the Chi Square test at Î± = 5%. Result : The results showed that there was a significant relationship between physical activity (OR = 8.07), stress level (OR = 9.62), exposure to cigarette smoke (OR = 4.02), obesity (OR=5.10), salt consumption (OR = 15.88), and consumption of fat (OR = 6.47) with hypertension in pregnant women at the Simpang IV Sipin health center, Jambi City in 2023. Conclusion : There is a relationship between physical activity, stress levels, exposure to cigarette smoke, obesity, salt consumption, fat consumption and the incidence of hypertension in pregnant women Keywords : Hypertension, pregnant women, risk factors.